Will Hunting's Fear abandonment and Chilhood Trauma in "Good Will Hunting" Movie by Lawrence Bender - Nikita Wahyu; Agnes Widyaningrum (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
Film is a form of modern literary work that combines visual and audio elements, enabling it to convey specific ideas, concepts, and messages to the public. Viewers, as recipients of the message, not only enjoy films as a means of entertainment but also often interpret them as representations of real life. This is due to the many films that present simple storylines, close to everyday life, yet still leave a deep impression. Thus, film has a dual function: as a medium of entertainment and a medium of social communication that voices various issues that arise in society. This research uses a context-oriented approach, namely a method of interpreting literary works that emphasizes the relationship between the text and the social and psychological contexts that underlie it. In this study, the analysis focuses on the main character, Will Hunting, in the film Good Will Hunting, who experiences fear of abandonment. The analysis is conducted through the framework of Litz and Keane's trauma response theory. Fear of abandonment is a form of psychological disorder that is generally eliminated from past traumatic experiences, such as rejection or neglect. This trauma then causes anxiety that affects interpersonal relationships in adulthood. The results show that individuals with a fear of being liked tend to take various precautions to reject new bonds and meaningful relationships. Will Hunting's character reflects a rejection and avoidance of emotional intimacy with others. He also employs defense mechanisms such as repression, rationalization, and sublimation to ward off potential self-destruction resulting from his internal conflict. By dwelling on painful memories, he builds a psychological barrier to protect himself, even though it ultimately limits the possibility of building healthy relationships.